An analysis of slang words found in the movie script of “the fast and the furious” by rob cohen - Syahputra, Denny; Suastini, Ni Wayan; Sulatra, I Komang (Institut Pariwisata dan Bisnis Internasional, 2021)
This study aimed at identifying the types of slang and the process of creating slang word found in a movie script entitled The Fast and The Furious by Rob Cohen. This study employed descriptive and qualitative method. The data of this study were obtained by watching and taking notes of slang word spoken by the characters in the movie “The Fast and The Furious”. There are two types of slang word, namely primary and secondary, using the theory by Chapman (2007), and in a matter of process of creating slang, the theory by Yule was adopted (1985). The data of this study were obtained by observation method through four steps, namely watching The Fast and The Furious. Next, finding and taking notes of slang words spoken by the characters in the movie The Fast and The Furious. Reading the online movie script and finally, the writer categorized the types of data. There were two types of slang words encountered, namely primary and secondary slang. The result of the study demonstrated that there are 5 slang words found in the movie The Fast and The Furious with 3 primary slang and 2 secondary slang.